2018
DOI: 10.3126/jcmsn.v14i4.22031
|View full text |Cite
|
Sign up to set email alerts
|

Complete Rockall score in predicting outcomes in acute upper gastrointestinal bleeding

Abstract: Background: Acute upper GI bleeding is a common medical emergency with a hospital mortality of approximately 10%. Higher mortality rate is associated with re-bleedinging. Complete Rockall scoring system identifies patients at higher risk of re-bleeding and mortality. Materials and Methods: This is a descriptive hospital based study conducted in Gastroenterology unit of College of Medical Sciences and Teaching Hospital, Bharatpur, Nepal from January 2012 to December 2014. It included 200 patients at random pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
0
1
Order By: Relevance
“…Mean arterial blood pressure was low (73.71±10.95) 12 and hypotension was noted in 14.8% 18 of patients at presentation. Patients were anemic in 16.5% in our study but in other studies, it was reported in 31% 19 of patients being severely anemic.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…Mean arterial blood pressure was low (73.71±10.95) 12 and hypotension was noted in 14.8% 18 of patients at presentation. Patients were anemic in 16.5% in our study but in other studies, it was reported in 31% 19 of patients being severely anemic.…”
Section: Resultscontrasting
confidence: 70%
“…17 In our study, 22.3% of patients received a blood transfusion. A higher percentage of blood transfusion in 77% 8 , 69.5% 18 , and 51.92% 19 have been reported in other studies.…”
Section: Resultssupporting
confidence: 46%
“…The Rockall scoring system is a comprehensive analysis of age, shock index, complications and other indicators of patients to accurately identify the potential bleeding risk of patients and effectively improve the prognosis. Studies have indicated that the Rockall score has been confirmed to be an accurate predictor of rebleeding and death [7]. Therefore, effective risk stratification of gastrointestinal bleeding by the Rockall score can help identify high-risk patients, thereby conducting closer monitoring, faster response, and improvement of prognosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Upper gastrointestinal bleeding (UGIB) is a lifethreatening condition and requires careful evaluation from the very first episode as an attempt to predict and reduce the risk of re-bleeding and death. 8 Several riskscoring systems exist to assess patients presenting with upper gastrointestinal hemorrhage.…”
mentioning
confidence: 99%